B55α/PP2A Limits Endothelial Cell Apoptosis During Vascular Remodeling: A Complementary Approach To Disrupt Pathological Vessels?. Issue 6 (28th August 2020) - Ehling, Manuel; Celus, Ward; Martín-Pérez, Rosa; Alba-Rovira, Roser; Willox, Sander; Ponti, Donatella; Cid, Maria C.; Jones, Elizabeth A.V.; Di Conza, Giusy; Mazzone, Massimiliano
Abstract : Rationale: How endothelial cells (ECs) migrate and form an immature vascular plexus has been extensively studied. Yet, mechanisms underlying vascular remodeling remain poorly established. A better understanding of these processes may lead to the design of novel therapeutic strategies complementary to current angiogenesis inhibitors. Objective: Starting from our previous observations that PP2A (protein phosphatase 2) regulates the HIF (hypoxia-inducible factor)/PHD-2 (prolyl hydroxylase 2)-constituted oxygen machinery, we hypothesized that this axis could play an important role during blood vessel formation, tissue perfusion, and oxygen restoration. Methods and Results: We show that the PP2A regulatory subunit B55α is at the crossroad between vessel pruning and vessel maturation. Blood vessels with high B55α counter cell stress conditions and thrive for stabilization and maturation. When B55α is inhibited, ECs cannot cope with cell stress and undergo apoptosis, leading to massive pruning of nascent blood vessels. Mechanistically, we found that the B55α/PP2A complex restrains PHD-2 activity, promoting EC survival in a HIF-dependent manner, and furthermore dephosphorylates p38, altogether protecting ECs against cell stress occurring, for example, during the onset of blood flow. In tumors, EC-specific B55α deficiency induces pruning of immature-like tumor blood vessels resulting in delayed tumor growth and metastasis, without affecting nonpathological vessels. Consistently, systemic administration of a pan-PP2A inhibitor disrupts vascular network formation and tumor progression in vivo without additional effects on B55α-deficient vessels. Conclusions: Our data underline a unique role of the B55α/PP2A phosphatase complex in vessel remodeling and suggest the use of PP2A-inhibitors as potent antiangiogenic drugs targeting specifically nascent blood vessels with a mode-of-action complementary to VEGF-R (vascular endothelial growth factor receptor)-targeted therapies. Abstract : Supplemental Digital Content is available in the text.